Crops adapted to the arid region - Chitty, Joseph Griffith (My University, 1905)
Introduction: The study of crop adaptation to the arid region is a Question that has been under much consideration by the student of agriculture for the past few years. The cry for more land for the oncoming generation is awakening the student to the fact that if possible this western land must be put under cultivation rather than that it be used entirely for grazing purposes. The soil of this western country is of fine texture and with little cultivation will produce good crops if the proper amount of moisture can be had. During the year there is usually enough rainfall to produce a crop but the irregularity of the rainfall does not warrant that a crop can be produced every year. The most important divisions of this subject are: 1. The irregularity of rainfall. 2. Conserving the soil moisture. 3. Method of tillage. 4. Effect of sub soiling. 5. Moisture required by crops. Conserving soil moisture by plowing. Shortly after the season's crop has been removed fall plowing should begin. By plowing early a mulch is formed which prevents evaporation, and also the fall rains will be taken into the soil and retained much better than if the soil were compact, aid percolation would be much more rapid. In a country where there is plenty of moisture this plan is not advisable as the moisture tends to develop nitrates and these if not saved by a cover crop will be lost by percolation.
Citation: Chitty, Joseph Griffith. Crops adapted to the arid region. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Irregularity of Rainfall; Conserving the soil Moisture; Method of Tillage; Effect of Subsoiling; Theses